Postinfusion monitoring costs by site of care for patients with relapsed/refractory large B-cell lymphoma receiving third- or later-line treatment with lisocabtagene maraleucel in the TRANSCEND NHL 001 and OUTREACH trials. Issue 9 (29th July 2021) - Palomba, M. Lia; Jun, Monika Parisi; Lymp, James; Nguyen, Andy; McGarvey, November; Gitlin, Matthew; Pelletier, Corey; Keating, Scott J.; Godwin, John
Abstract: This retrospective study estimated postinfusion health care resource utilization (HCRU) by site of care among 303 patients with relapsed/refractory large B-cell lymphoma who received third- or later-line treatment with lisocabtagene maraleucel (liso-cel) in the TRANSCEND NHL 001 and OUTREACH trials. Inpatients ( n  = 256) had higher rates of hospitalization versus outpatients ( n  = 47; >99% vs 62%), by definition, and higher rates of tocilizumab use for cytokine release syndrome and/or neurological events (22% vs 9%). Rates of intensive care unit admission, corticosteroid use, vasopressor use, hemodialysis, and intubation were generally low and similar between groups. Median (range) total hospital length of stay was 15 (0–88) days (inpatients) and 4 (0–77) days (outpatients). Over 6 months, estimated mean postinfusion cost of care was $89, 535 (inpatients) and $36, 702 (outpatients). Most costs were incurred in the first month post infusion (inpatients, $50, 369 [56%]; outpatients, $19, 837 [54%]). Lower overall HCRU was observed with outpatient postinfusion monitoring.